Intercropping of Cereals and Legumes for Forage Production - Hamdollah ESKANDARI; Ahmad GHANBARI; Abdollah JAVANMARD (Notulae Scientia Biologicae, 2009)
Cereals are high important in feeding ruminant animals for their high dry matter production and low cost. However, cereals forage is poor in protein content which shows their low quality and nutritive value. Regarding to high feed costs of protein supplementations, legumes can be used in livestock nutrition for their high protein content and, thus, providing cost saving. Since legumes have low dry matter yield, acceptable forage yield and quality can obtained from intercropping of cereals and legumes compared with their sole crops. In this paper, forage quality indicators and different factors affecting forage quality are discussed. Forage production and quality of different cereals-legumes intercropping are also reviewed, where; different legumes had different effect on forage quality when intercropped with specific cereal. Regarding to forage quality and quantity, different cereals also led to different production of forage. A number of factors which must be noticified in selecting cereal-legume intercropping compositions, especially for forage production, were considered.